Tradisi Tahlilan Upaya Menyambung Silaturahmi - Andi Warisno (Pascasarjana IAIN Metro, 2017)
Indonesia is a unitary State of diversity. Indonesia consists of a wide range of cultures, regional languages, races, ethnic groups, religions and beliefs, etc. However, Indonesia is able to unify the various diversity in accordance with the slogan of the Indonesian nation